2014
DOI: 10.1037/hea0000083
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents coping with cancer: Self- and parent reports of coping and anxiety/depression.

Abstract: Objective The diagnosis and treatment of cancer present children and adolescents with significant stress. However, research on the ways that children and adolescents cope with cancer-related stress has not yielded clear findings on the efficacy of different coping strategies, and has been limited by reliance primarily on self-reports of both coping and distress. To address this gap, the current study used a control-based model of coping to examine self- and parent reports of child/adolescent coping and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
19

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 44 publications
6
93
0
19
Order By: Relevance
“…During treatment, the child is isolated from his/her school, friends, and family members. All these factors impair the quality of life of the children and their families and induce psychological problems (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…During treatment, the child is isolated from his/her school, friends, and family members. All these factors impair the quality of life of the children and their families and induce psychological problems (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Coping behaviors are used for people who suffer from stress and want to manage their own internal and external pressure; this issue is of high im-portance in patients with cancer suffering from stress (15,16). Coping behaviors are dynamic, continuous, and progressive; the willingness of a person to compromise with the continuous changes happens in life.…”
Section: Introductionmentioning
confidence: 99%
“…Compas et al 6 identified that the cancer diagnosis of a child can be distressing for the family as a whole. Similarly other studies 5,7 noted that the adjustment to having a child with cancer can have a significant impact on the psychological well-being of the family members and their functioning, within the household and the community.…”
mentioning
confidence: 99%